Propuesta Urbana para una Ciudad Universitaria caso de estudio parroquia Lizarzaburu - Riobamba - Hidalgo Chávez, Carlos Eduardo (2024)
Due to the geographical location, accessibility, and diversity of university careers, Riobamba has become a city of student destination; however, the uncontrolled growth and lack of planning in the town of Riobamba has generated an irregular development both in its morphology and infrastructure, with significant deficiencies in services and equipment and large urban gaps that have produced a tremendous social fragmentation, insecurity, high environmental pollution and inequity, leaving susceptible to the population in which there is a high rate of university students. For this reason, the purpose of this research is to develop an urban proposal for a university city within a delimited area in the parish of Lizarzaburu, with which intended to carry out urban planning since in the area to intervene there is a high rate of urban voids owing to poor planning because it is located near the urban edge where conditions are different at a social and environmental level compared to the urban center, these sectors have been developed mainly by informal settlements, either by migration from the countryside to the city or by the high price of lots in the center of the town. Therefore, the proposal aims to develop strategies based on an urban analysis at the macro, meso, and micro scale of the sector, in which it is intended to understand the existing deficiencies and potentialities, in addition to conducting a literature review and study of references that will serve as support for the development of the urban proposal for a university city with the application of guidelines that will be concluded with urban interventions and Implementation of new axes and public spaces, in addition to making modifications in the irregular sections to generate continuity and eliminate spatial segregation in the sector to promote the development of the inhabitants of the industry to be intervened in all areas and improve their quality of life.